6(x-7)+7=6x-7(7-x)

Simple and best practice solution for 6(x-7)+7=6x-7(7-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-7)+7=6x-7(7-x) equation:


Simplifying
6(x + -7) + 7 = 6x + -7(7 + -1x)

Reorder the terms:
6(-7 + x) + 7 = 6x + -7(7 + -1x)
(-7 * 6 + x * 6) + 7 = 6x + -7(7 + -1x)
(-42 + 6x) + 7 = 6x + -7(7 + -1x)

Reorder the terms:
-42 + 7 + 6x = 6x + -7(7 + -1x)

Combine like terms: -42 + 7 = -35
-35 + 6x = 6x + -7(7 + -1x)
-35 + 6x = 6x + (7 * -7 + -1x * -7)
-35 + 6x = 6x + (-49 + 7x)

Reorder the terms:
-35 + 6x = -49 + 6x + 7x

Combine like terms: 6x + 7x = 13x
-35 + 6x = -49 + 13x

Solving
-35 + 6x = -49 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
-35 + 6x + -13x = -49 + 13x + -13x

Combine like terms: 6x + -13x = -7x
-35 + -7x = -49 + 13x + -13x

Combine like terms: 13x + -13x = 0
-35 + -7x = -49 + 0
-35 + -7x = -49

Add '35' to each side of the equation.
-35 + 35 + -7x = -49 + 35

Combine like terms: -35 + 35 = 0
0 + -7x = -49 + 35
-7x = -49 + 35

Combine like terms: -49 + 35 = -14
-7x = -14

Divide each side by '-7'.
x = 2

Simplifying
x = 2

See similar equations:

| 27+22x/3 | | G^2+5g-6=0 | | z+33=15 | | 8=-.75x+14 | | y-1.6=10.6 | | 2/7y=-10 | | (x^5-4x^3)(8x^2-32)=0 | | x+0.16(60)=0.4(60+x) | | 26=214-x | | 1/2x+1/5x=31-1/3x | | 14s^2-10s=2s | | (7b-1)-2(3b+3)=-7 | | 5w^2-3-14w=0 | | -10x-12y=12 | | 0.1x+0.8=1.9 | | 4x+4=-8+2x+24 | | g/4=56 | | x/15=60 | | 9m^4n^5-27m^2n^3= | | 9x^2=-6x+8 | | 84-119=-6(-6y)-19(2y)+y | | 45/x=5 | | 6x-2=8x+9 | | 75=-5s | | 834-119=-6(-6y)-19(2y)+y | | 84(3-x)+105x=4998 | | 80Xx=45 | | -3w-1/2=5/2w-1/3 | | Ax+b=cx+b | | 300/1760=x/1 | | T(u+3v)=w-5u | | x+15=50 |

Equations solver categories